2020
DOI: 10.1088/2053-1591/ab654a
|View full text |Cite
|
Sign up to set email alerts
|

Parametric studies on dry sliding wear behaviour of Al-7075 alloy matrix composite using S/N ratio and ANOVA analysis

Abstract: Al7075/10 wt% TiO 2 alloy composite has been fabricated by the stir casting method to investigate the influence of wear parameters. The microstructure of the produced composite was analyzed by scanning electronic microscopy. A pin-on-disc rig was used to carry out the wear test on produced composite under dry sliding conditions. The three wear control parameters such as load, sliding velocity and sliding distance were chosen to study the effects on the wear rate and coefficient of friction of composite. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…ANOVA is a typical algebraic method which is used to determine the impact of process parameters on the desired output responses. 40,43 In this study, ANOVA has been employed to estimate the percentage contribution of cutting parameters namely cutting speed (v), feed rate (f), and depth of cut (d) on grey relational grade and grey fuzzy reasoning grade while CNC turning process of SS303. The percentage contribution of each parameter has computed from the ratio of individual factor's Sum of Squares (SS) value to the total SS values.…”
Section: Resultsmentioning
confidence: 99%
“…ANOVA is a typical algebraic method which is used to determine the impact of process parameters on the desired output responses. 40,43 In this study, ANOVA has been employed to estimate the percentage contribution of cutting parameters namely cutting speed (v), feed rate (f), and depth of cut (d) on grey relational grade and grey fuzzy reasoning grade while CNC turning process of SS303. The percentage contribution of each parameter has computed from the ratio of individual factor's Sum of Squares (SS) value to the total SS values.…”
Section: Resultsmentioning
confidence: 99%
“…The ANOVA results for the 49 managers' answers to the four questions on decision-making, which were part of the semi-structured face-to-face interviews comprising 16 questions, indicated that significant differences existed among the groups; therefore, Scheffe's test was used as an ad hoc analysis to identify which specific groups differed. A significance level of 5% was chosen to determine statistical significance for all hypothesis testing (Alagarsamy and Ravichandran, 2020). The statistical analysis showed that overall, the managerial information behavior when making decisions is similar among the three shipping sectors.…”
Section: Semi-structured Interviews: Anova Analysismentioning
confidence: 99%
“…19 To determine the optimum range of factors for obtain less WR, the various optimization techiniques are employed. Alagarsamy and Ravichandran 20 optimized the control variables on WR of TiO 2 reinforced AMCs by using Taguchi method and reported that the less WR is obtained at a load of 9.81 N with a velocity of 2.82 m s −1 and a sliding distance of 1000 m. Neeraj Kumar et al 21 studied the wear behaviour of B 4 C incorporated Al-Mg-Si composites and observed that the WR increases with increase in sliding distance. However, the inclusion of B 4 C particles decreasing the WR due to enhanced the surface hardness.…”
Section: Introductionmentioning
confidence: 99%